In Vitro Pro-apoptotic and Anti-migratory Effects of Ficus deltoidea L. Plant Extracts on the Human Prostate Cancer Cell Lines PC3 - Hanafi, Mohd M. M.; Afzan, Adlin; Yaakob, Harisun; Aziz, Ramlan; Sarmidi, Mohamad R.; Wolfender, Jean-Luc; Prieto, Jose M. (Frontiers in Pharmacology, 2017)
This study aims to evaluate the in vitro cytotoxic and anti-migratory effects of Ficus deltoidea L. on prostate cancer cells, identify the active compound/s and characterise their mechanism of actions. Two farmed varieties were studied, var. angustifolia (FD1) and var. deltoidea (FD2). Their crude methanolic extracts were partitioned into n-hexane (FD1h, FD2h) chloroform (FD1c, FD2c) and aqueous extracts (FD1a, FD2a). Antiproliferative fractions (IC50<30 μg/mL, SRB staining of PC3 cells) were further fractionated. Active compound/s were dereplicated using spectroscopic methods. In-vitro mechanistic studies on PC3 and/or LNCaP cells included: Annexin V-FITC staining, MMP depolarization measurements, activity of caspases 3 and 7, nuclear DNA fragmentation and cell cycle analysis, modulation of Bax, Bcl-2, Smac/Diablo and Alox-5 mRNA gene expression by RT-PCR. Effects of cytotoxic fractions on 2D migration and 3D invasion were tested by exclusion assays and modified Boyden chamber, respectively Their mechanisms of action on these tests were further studied by measuring the expression VEGF-A, CXCR4 and CXCL12 in PC3 cells by RT-PCR. FD1c and FD2c extracts induced cell death (P<0.05) via apoptosis as evidenced by nuclear DNA fragmentation. This was accompanied by an increase in MMP depolarization (P < 0.05), activation of caspases 3 and 7 (P<0.05) in both PC3 and LNCaP cell lines. All active plant extracts up-regulated Bax and Smac/DIABLO, down-regulated Bcl-2 (P<0.05). Both FD1c and FD2c were not cytotoxic against normal human fibroblast cells (HDFa) at the tested concentrations. Both plant extracts inhibited both migration and invasion of PC3 cells (P<0.05). These effects were accompanied by down-regulation of both VEGF-A and CXCL-12 gene expressions (P<0.001). LC-MS dereplication using taxonomy filters and molecular networking databases identified isovitexin in FD1c; and oleanolic acid, moretenol, betulin, lupenone and lupeol in FD2c. In conclusion, FD1c and FD2c were able to overcome three main hallmarks of cancer in PC3 cells: (1) apoptosis by activating of the intrinsic pathway, (2) inhibition of both migration and invasion by modulating the CXCL12-CXCR4 axis, and (3) inhibiting angiogenesis by modulating VEGF-A expression. Moreover, isovitexin is here reported for the first time as an antiproliferative principle (IC50=43 μg/mL, SRB staining of PC3 cells).